Determinan Kejadian Preeklampsia pada Ibu Hamil - Nurdin, St. Surya Indah; Dunggio, Ratna; Batiti, Sarni; Sondakh, Levana; Ahmad, Zul Fikar (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2021)
Preeclampsia is an increase in blood pressure in pregnant women and excess levels of protein in the urine (proteinuria). This study aims to assess the factors associated with the incidence of preeclampsia. This is an analytical observational study with a case control study approach. This study was carried out in January-September 2018. The sample in this study was 62 people, 31 case samples and 31 control samples. Sample was selected used simple random sampling technique. Data analysis using chi-square test. The results of this study showed that there was a relationship between obesity, parity, and history of ANC with the incidence of preeclampsia with p-value <0.05. Obesity is 7.2 times more at risk of developing preeclampsia (OR = 7,200 CI 95% = 2,182-23,755). Multigravida (OR = 0.044 95% CI: 0.011-0.182) and a history of complete ANC (OR = 0.057 95% CI: 0.011-0.281) were protective factors for the incidence of preeclampsia. To prevent the incidence of preeclampsia, it is necessary to increase education and literacy on risk factor prevention, including improving clean and healthy living behavior.